The Attitudes of Non Specialist EFL Post-Graduate Iraqi Students About Edmodo and their Utilizing for Learning the English Language - البياتي، زينة عبد علي داود (جامعة الانبار - كلية التربية للعلوم الإنسانية, 2022)
هدفت هذه الدراسة إلى التحقيق في اتجاهات طلاب الدراسات العليا العراقيين غير المتخصصين في اللغة الإنجليزية كلغة أجنبية حول استخدام المنصة التعليمية (إدمودو Edmodo) كأداة لتعلم اللغة الإنجليزية. كما هدفت في معرفة تأثير الجنس (ذكورا وإناثا) والتخصص (الأقسام العلمية والإنسانية) لطلاب الدراسات العليا غير المتخصصين في اللغة الإنجليزية كلغة أجنبية على استخدام (إدمودو Edmodo) كأداة لتعلم اللغة الإنكليزية. خلال العام الدراسي 2020-2021، شارك في هذه الدراسة (80) طالب وطالبة في مرحلة الدراسات عليا غير متخصصين في اللغة الإنكليزية كلغة أجنبية من كلية التربية في الجامعة المستنصرية في العراق. تم تطبيق هذه الأداة التعليمية في العراق وقت (كوفيد-19) على جميع الجامعات العراقية في مرحلة الدراسات العليا. تم جمع البيانات من خلال استبيان، وأشار تحليل النتائج إلى اتجاهات إيجابية تجاه استخدام المنصة التعليمية (إدمودو Edmodo) كأداة لتعلم اللغة الإنجليزية. أظهرت نتائج هذه الدراسة أن الارتباط السلوكي (BE) قد حصل على متوسط حسابي (M = 4.22)، وتنمية المهارات اللغوية (DLS) قد حصلت على متوسط حسابي (M = 4.11)، وتعلم اللغويات باستخدام تقنية الادمودو (LLET) قد حصلت على متوسط حسابي (M = 3.84) وهذا يدل على أن هذه المكونات الثلاثة قد حصلت أعلى متوسطات من بين مكونات مقياس الاتجاهات الخمسة حول استخدام المنصة التعليمية (ادمودو) كأداة لتعليم اللغة الإنكليزية. أخيرا، تم حساب الكفاءة اللغوية (LC) والذي حصل على متوسط حسابي (M = 3.84) وكفاءة التقنية للادمودو (ETC) والذي حصل على متوسط حسابي (3.78 = M) والتي جاءت في أخر الترتيب في اتجاهات الطلبة. وبحسب نتائج هذه الدراسة، كان هناك فرق ذو دلالة إحصائية بين متوسط الأقسام الإنسانية والأقسام العلمية لاتجاهات طلاب الدراسات العليا غير المتخصصين في اللغة الإنجليزية كلغة أجنبية نحو استخدام Edmodo كأداة لتعلم اللغة الإنجليزية. كذلك، لم يكن هناك فروق ذات دلالة إحصائية في اتجاهات الطلاب والطالبات الذين يستخدمون Edmodo كأداة لتعلم اللغة الإنجليزية. وقد قدم الباحث بعض الآثار التربوية والدراسات البحثية المستقبلية. This study was purposed at investigate the attitudes of Iraqi non specialist EFL post-graduate students about Edmodo and their utilizing for learning the English language. The second objective was to investigate the influence of gender (male and female) and major (scientific and humanitarian departments) of non-specialist EFL post-graduate students on utilizing Edmodo as an implement of learning language. During the academic year 2020–2021, (80) non specialist EFL post-graduate students from the College of Education at Al-Mustansirya University in Iraq participated in this study. This educational tool was applied in Iraq at the time of (Covid-19) to all Iraqi universities in the post-graduate stage. Data were gathered through a questionnaire, and analysis of the results indicated favorable attitudes toward utilizing Edmodo as an implement of learning English language. The results of this study showed that the Behavioral Engagement (BE for short) (M= 4.22), Developing Language Skills (DLS for short) (M= 4.11), and Learning Linguistics with Edmodo Technology (LLET for short) (M= 3.84) had the highest mean averages among the five attitude scale components. Finally, the Linguistics Confidence (LC for short) (M= 3.84) and Edmodo Technology Confidence (ETC for short) (M= 3.78) were calculated. According to the findings of this study, there was a statistically significant difference between the mean of the humanitarian departments and scientific departments of non-specialist EFL post-graduate students' attitudes toward utilizing Edmodo as an implement of learning English language. Likewise, there was no statistically significant difference in the attitudes of male and female students which utilizing Edmodo as an implement of learning English language. This study concludes with some pedagogical implications and and future research studies
Keywords: طلبة الدراسات العليا -- المنصات التعليمية -- منصة إدمودو -- تعلم اللغة الإنجليزية